Preoperative Evaluation of the Effects of Sigmoid Sinus Ligation with both Endovascular and Open-Field Occlusion Tests before Removal of Petroclival Tumors - Shitara, Satoshi; Inoue, Takuro; Tanaka, Toshiki; Hirai, Hisao; Fukushima, Takanori (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Surgery for petroclival tumors is very challenging for neurosurgeons because the position of the tumor in relation to the brainstem, cranial nerves, and posterior fossa vessels greatly restricts the surgical field. Some papers have described using sigmoid sinus ligation to open the surgical field; however, pre- and intraoperative evaluations of the safety of ligation have been limited, despite the risk of complications from venous insufficiency. Here, we describe our method of preoperatively evaluating the potential safety of a retrolabyrinthine transsigmoid approach with nondominant ipsilateral sigmoid sinus ligation (RLTSwSSL).Methods A retrospective review was conducted on petroclival tumors treated over a 5-year period with RLTSwSSL after evaluation with both an endovascular balloon occlusion test (BOT) and an open-field sinus clipping occlusion test (COT). Changes in pressure of < 10 mm Hg and the absence of neurodegeneration during the tests indicated that it would be safe to proceed with permanent ligation.Results Four patients with large petroclival tumors underwent surgery via RLTSwSSL after detailed preoperative evaluations with both BOT and COT. All patients had uneventful courses of recovery without developing any complications derived from venous insufficiency.Conclusion In our case series, we have described a protocol for using both BOT and COT to evaluate the likely outcomes after sigmoid sinus ligation and thereby to improve safety. Further studies are needed to establish definite criteria for both occlusion tests that will ensure good outcomes.
Keywords: balloon occlusion test; sinus ligation; skull base surgery; open-field occlusion test